2014
DOI: 10.1186/1471-2490-14-11
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy and tolerability of intravesical Bacillus Calmette-Guerin (BCG) - RIVM strain: induction and maintenance protocol in high grade and recurrent low grade non-muscle invasive bladder cancer (NMIBC)

Abstract: BackgroundBCG-RIVM strain was used in many treatment protocols for non-muscle invasive bladder cancer only as induction courses. Cho et al. (Anticancer Res 2012) compared BCG-RIVM induction and 'standard' maintenance (Lamm et al., J Urol. 2000) to mitomycin C. They found no statistically significant differences regarding disease recurrence and progression. The purpose of our study was to determine the efficacy & tolerability of this specific BCG RIVM strain, using six-weekly, induction course and single monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
1
16
0
2
Order By: Relevance
“…In our cohort, the 5-year RFS rate was 65%, which is in concordance with current literature with rates ranging between 59 and 69% with the other strains [16,21,25]. Similar, the 5-year PFS rate of 81% is in line with recent studies reporting rates between 72 and 84% with other strains [25,26,27,28,29].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our cohort, the 5-year RFS rate was 65%, which is in concordance with current literature with rates ranging between 59 and 69% with the other strains [16,21,25]. Similar, the 5-year PFS rate of 81% is in line with recent studies reporting rates between 72 and 84% with other strains [25,26,27,28,29].…”
Section: Discussionsupporting
confidence: 81%
“…Initially introduced in 1986, studies including this strain were basically limited to induction courses only. Recently, it has been shown that the RIVM strain for induction and maintenance leads to similar outcomes with regard to recurrence and PFS than other strains [21]. Unfortunately, the production has been on hold since the last quarter of 2014.…”
Section: Discussionmentioning
confidence: 99%
“…However, with subsequent instillations (as for the maintenance therapy) the immune stimulation peaks at 3 weeks and is suppressed at weeks 4 and 5. 25 In fact, we observed a recurrence rate of 22.2% and 2.94% in patients treated with monthly and SWOG maintenance protocols ( p = 0.217). Additionally, patients treated with the SWOG protocol had a progression rate of 2.94% and the monthly protocol had 11.1% ( p = 0.775).…”
Section: Discussionmentioning
confidence: 71%
“…Õîòÿ A. Sengiku et al [88] íå îáíàðóaeèëè ðàçíèöû â ýôôåêòèâíîñòè è áåçîïàñíîñòè âàêöèíû ÁÖAE Connaught è ÁÖAE Tokyo íà áëèçêèõ ïî êëèíè÷åñêîé õàðàêòåðèñòèêå ãðóïïàõ áîëüíûõ ÐÌÏ. Çíà÷èòåëüíîå ïðåèìóùåñòâî âàêöèíû ÁÖAE-RIVM ïðîäåìîíñòðèðîâàíî â ÊÈ, ïðîâåäåííûõ N. B. Farah et al [29], îäíàêî âûâîäû àâòîðîâ áàçèðóþòñÿ íà ðåçóëüòàòàõ, ïîëó÷åííûõ íà ìàëîì êîëè÷åñòâå íàáëþäåíèé.  äåòàëüíîì îáçîðå C. Gan et al [31] ïðîàíàëèçèðîâàíû ðàçëè÷èÿ ðàçíûõ øòàììîâ è âûñêàçàíî ïîëîaeåíèå î òîì, ÷òî òîëüêî íîâûå çíàíèÿ îá èììóíîãåíåòèêå, ñòðóêòóðå, ôóíêöèÿõ ìèêîáàêòåðèè è ïðèíöèïàõ åå âçàèìîäåéñòâèÿ ñ ìàêðîîðãàíèçìîì ìîãóò îáúÿñíèòü çíà÷èìîñòü ýòèõ ðàçëè÷èé äëÿ êëèíè÷åñêîé ïðàêòèêè, à òàêaeå èäåíòèôèöèðîâàòü áèîëîãè÷åñêèå ìàðêåðû ðåàêòîãåííîñòè è ýôôåêòèâíîñòè âàêöèíû ÁÖAE, ïðèìåíÿåìîé ïðè ÐÌÏ.…”
Section: ýôôåêòèâíîñòü è áåçîïàñíîñòü âàêöèíû áöAeunclassified